Multi-Segment Foam Flow Field in Ambient Pressure Polymer Exchange Membrane Fuel Cell - Cheng, Chih-Kai; Jao, Ting-Chu; Chi, Pei-Hung; Hsu, Che-Jung; Weng, Fang-Bor; Su, Ay; Heng, Tsao (Journal of Technology Innovations in Renewable Energy, 2013)
In order to produce low-cost flow field plates for polymer electrolyte membrane fuel cells, we used nickel foam in this study rather than conventional flow field. Nickel foam has high electron conductivity, thermal conductivity, and mechanical strength. Electrochemical impedance spectrum analysis is carried out to evidence the use on flow field plates of nickel foam. From the impedance fitting results, the nickel foam cases showed the lower contact resistance than the serpentine. However, such plates have poor performance at low temperatures and ambient pressure. In order to overcome this, a multi-segment foam flow field is designed in this study. This increased the performance of the polarization curve by 70% from 162 to 275.5 mw cm-2 than the original nickel foam design. Also, the mass transfer resistance was reduced, and the Warburg impedance value of the operation voltage decreased by 0.4 V. The numerical analysis results demonstrate that increased segment numbers can increase the performance of the multi-segment foam flow field.